Doing political ethnography in a difficult climate: A Turkish case study. (June 2016) - Tittensor, David
In recent times, there has been a great deal of soul-searching about terms such as 'deception' and 'informed consent' and, consequently, ethics review boards have applied the biomedical ethics model to the ethnographic endeavour and the wider social sciences. However, these new strictures are problematic, particularly when undertaking politically sensitive research. Drawing on 13 months of ethnographic fieldwork in Turkey on the maligned religious organization known as the Gülen Movement, this paper will argue that informed consent is not always the most appropriate approach when researching hard-to-reach or hidden communities. Rather, it will seek to illustrate that rapport, trust, friendship and reciprocity are worthy substitutes.